Small and Large Animal Veterinarian Perceptions of Antimicrobial Use Metrics for Hospital-Based Stewardship in the United States - Redding, Laurel E.; Muller, Brandi M.; Szymczak, Julia E. (Frontiers in Veterinary Science, 2020)
Background: Robust measurement and tracking of antimicrobial use (AU) is a fundamental component of stewardship interventions. Feeding back AU metrics to individual clinicians is a common approach to changing prescribing behavior. Metrics must be meaningful and comprehensible to clinicians. Little is known how veterinary clinicians think about AU metrics in the context of antimicrobial stewardship. Objective: To identify veterinary clinicians’ attitudes towards audit and feedback of AU metrics, their perceptions of different AU metrics and their response to receiving an individualized prescribing report. Methods: Semi-structured interviews were conducted with veterinarians working at two hospitals in the Eastern United States. Interviews elicited perceptions of antimicrobial stewardship in veterinary medicine. Respondents were shown a personalized AU Report characterizing their prescribing patterns relative to their peers, and were asked to respond. Interviews were recorded, transcribed and analyzed using the framework method with matrices. Results: Semi-structured interviews were conducted with 34 veterinary clinicians (22 small animal and 12 large animal). Respondents generally felt positively about the reports and were interested in seeing how their prescribing compared to that of their peers. Many respondents expressed doubt that the reports accurately captured the complexities of their prescribing decisions and found metrics associated with animal daily doses (ADDs) confusing. Only 13 (38.2%) respondents felt the reports would change how they used antimicrobials. When asked how the impact of the reports could be optimized, respondents recommended providing a more detailed explanation of how the AU metrics were derived, education prior to report roll-out, guidance on how to interpret the metrics, and the development of meaningful benchmarks for goal-setting. Conclusions: These findings provide important insight that can be used to design veterinary-specific AU metrics as part of a stewardship intervention that are meaningful to clinicians and likely to promote judicious prescribing.